1996
DOI: 10.1111/j.1600-0897.1996.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Expression by Models of Human Trophoblast as Assessed by a Semiquantitative Reverse Transcription‐Polymerase Chain Reaction Technique

Abstract: Human choriocarcinoma cells and term trophoblast express cytokines that may regulate critical reproductive events. Expression of inflammatory cytokines such as IL-1, TNF-alpha, and IFN-gamma by term trophoblast could trigger labor or be a consequence of labor-associated events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Determination of TNFa mRNA levels by RT-PCR has previously been used for estimating the TNFa expression by human trophoblasts (King et al 1995, Bennett et al 1996. Comparing expression of TNFa mRNA on cultured CT at a pO 2 of 38 mmHg with that at 140 mmHg, we found that cells from an uncomplicated placenta expressed significantly less (P!0.05, a 35% decrease) at 38 mmHg and that IUGR cells expressed more (P!0.05, a 55% increase) at 38 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of TNFa mRNA levels by RT-PCR has previously been used for estimating the TNFa expression by human trophoblasts (King et al 1995, Bennett et al 1996. Comparing expression of TNFa mRNA on cultured CT at a pO 2 of 38 mmHg with that at 140 mmHg, we found that cells from an uncomplicated placenta expressed significantly less (P!0.05, a 35% decrease) at 38 mmHg and that IUGR cells expressed more (P!0.05, a 55% increase) at 38 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…44 As we described previously, FK-stimulated BeWo cells also express markers of typical syncytiotrophoblast cells, such as human chorionic gonadotrophin and markedly reduced E-cadherin expression. 38 Moreover, BeWo cells express IL-10 at the mRNA and the protein levels 45,46 and a recent study demonstrated that this cell line responds very well to exogenous IL-10. 47 Thus, these similarities to trophoblast cells support the use of BeWo cells as a valid and suitable model for studying different aspects of villous cytotrophoblast differentiation and function.…”
Section: Isolation and Purification Of Term Villous Cytotrophoblastsmentioning
confidence: 99%
“…As it is known that upregulation of Th1 activity responses was also shown in vitro by increased IFN-␥ [20]. Increased concentrations of this cytokine are harmful for pregnancy, causing fetal resorption in a murine model of recurrent spontaneous abortion [25], and could also be responsible for induction of trophoblast apoptosis [26]. Indeed, NO inhibits the secretion of IFN-␥ by Th1 cells [27].…”
Section: Discussionmentioning
confidence: 98%